A giant left atrial myxoma causing mitral valve pseudostenosis - a mimicker - Basel Abdelazeem; Hafiz Khan; Hameem Changezi; Ahmad Munir (Greater Baltimore Medical Center, 2021)
The clinical features of cardiac myxoma vary significantly from asymptomatic to severe cardiovascular complications like atrioventricular valve obstruction and thromboembolism depending on the location, size, and mobility of the tumor. Echocardiography is the diagnostic study of choice, and surgical resection is the method of choice to prevent complications. We report a case of a 47-year-old female who presented with exertional dyspnea, malaise, and weight loss. Physical examination was significant for jugular venous distension, basal crackles in lungs, 2+ pedal edema, and rumbling diastolic murmur at apex. CT of the chest revealed a hypodense filling defect in the left atrium. Transthoracic echocardiogram showed a 5.5 × 4.5 cm mobile density, likely myxoma, attached to the interatrial septum and prolapsing into the left ventricle during the diastolic phase, causing functional mitral stenosis. She underwent a resection of cardiac myxoma. The histopathology report confirmed the diagnosis of myxoma, and post-operative recovery was uneventful.